Feasibility Test of Papaya Microgreens (Carica papaya L. var. Callina) As Functional Foods - sujarwati, Sujarwati; Mayta Novaliza Isda; Retno Ayu Wulandari; Anisa Sholihatul Muawanah (Universitas Nusa Bangsa, 2025)
Papaya seeds have the potential to be developed as microgreens. Microgreens are classified as functional foods because they contain at least ten times more phytochemicals and vitamins than mature plants of the same species. This study aims to analyze the feasibility of Callina papaya microgreens as functional food based on proximate analysis, antioxidant activity, and antioxidant compound content. Proximate analysis was conducted by testing the moisture content (thermogravimetric), ash (dry soaking), protein (Kjeldahl method), fat (soxhlet method), and carbohydrate (by difference). The antioxidant activity test used the DPPH (2,2-diphenyl-1-picrylhydrazyl) method. Analysis of antioxidant compounds included testing vitamin C levels (spectrophotometry) and chlorophyll levels (portable chlorophyll meter). Flavonoid, alkaloid, and tannin compounds were tested qualitatively. Proximate analysis of papaya microgreens on dry weight contained 57.35% water, 0.48% ash, 3.46% carbohydrate, 13.45% fat, and 25.28% protein. Papaya microgreens in wet weight percent contained 94.35% water, 0.03% ash, 3.43% carbohydrate, 0.76% fat, and 1.43% protein. Papaya microgreens have very strong antioxidant activity with an IC50 value of 2.058 ppm. Antioxidant compounds in papaya microgreens are vitamin C (1.152%), chlorophyll (32.56 μmol/m²), flavonoids, and alkaloids, but tannins are not present. Based on the results of proximate analysis, antioxidant activity test, and antioxidant compounds, it can be concluded that papaya microgreens are feasible as functional food because it meet the requirements of functional foods, which contain physiologically active compounds and can provide health benefits.